Mitigation of Salt Stress in Proso Millet (Panicum miliaceum L.) By Exogenous 40-47 Application of Ascorbic Acid - Alam, M M; Masud, A A C; Hasanuzzaman, Mirza (Bangladesh Agronomy Journal, 2025)
Salinity is one of the most detrimental environmental factors that limits the growth and productivity of crops. Ascorbic acid (AsA) is a vital antioxidant of plants, which prevents the oxidative damage caused by salinity and improves plant growth performance. A semi-controlled experiment was conducted to evaluate the impact of salt stress (150 and 300 mM NaCl; S1 and S2, respectively) and AsA (250 and 500 μΜ; AsA1 and AsA2, respectively) on the seedling growth, physiological attributes, and yield of proso millet. The present study revealed that the salinity hampered the physiological processes and resulted in the reduction in yield attributes, while the application of AsA in salt-stressed plants improved the plant height, fresh and dry weight, leaf relative water content (RWC) and SPAD value, as well as yield contributing attributes. Foliar applications AsA at 10 days intervals for two times reported with enhanced plant parameters. Furthermore, the highest plant growth and yield attributes were observed while plants were sprayed with 500 μΜ AsA under salt stress. This study indicated that the exogenous addition of AsA can be a useful strategy to promote plant phenotypic characters and yield contributing characters of proso millet cultivated under saline regimes. Bangladesh Agron. J. 2024, 27(1): 40-47